Western Political Thought on the Scales of Thought A Critical of the Book Modern Western Political Thought: The Dialectic of Ideas - Farhad Zivyar; Mostafa Rezaee Hosseinabadi; Amir Etemadi Bozorg (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In her Book, Modern Western Political Thought, Alireza Ismailzad has written a relatively comprehensive look at the developments in political thought in the West from the seventeenth century to the postmodern situation. The main premise in the critique of this book is based on the necessity of producing such works. Because of the existence of a large number of books in the field of Western Political Thought, including authorship and translation, the importance of innovation in the production of new works is doubled. Does this mean that there is basically a new need for rethinking in this area? And, does this book open a new window on Western Political Thought? Regardless of its strengths, the book has objections to chronological, thematic, thematic classification, how modern political thought was formed and evolved in the West, the choice of political thinkers, and the methodology of analyzing and interpreting the findings. For example, ignoring the theoretical foundations of the emergence of modern political thought such as the renaissance, not mentioning the theories of thinkers such as Luther, Machiavelli, and Hobbes, lack of sociological approach, and most importantly, the exclusion of the basic foundations of modern political thought, including politics, government, sovereignty, identity, nationality, etc. are the most prominent shortcomings of the book.